Maternity waiting homes in times of crisis: Can current models meet women's needs?. Issue 4 (July 2021) - Wild, Kayli; Kurji, Jaameeta
Abstract: Background: Maternity waiting homes (MWHs) located close to birthing facilities are a conditional recommendation by the World Health Organisation, based on very low-quality evidence that they contribute to improvements in maternal or perinatal health outcomes. In addition, several studies suggest that more vulnerable women are less likely to use them. Yet significant investments continue to be made in building and running MWHs within conflict-affected and under-resourced health systems. Aims: We critically examine the literature to shed light on the challenges and opportunities provided by MWHs during health emergencies and in conflict situations. Findings and discussion: MWHs are difficult to utilise during crises because they require women to be away from home, are often designed as dormitories, can lack security and be over-crowded. Some MWHs have been adapted during situations of political conflict to incorporate birthing and broader reproductive health care, thereby improving the availability of care away from over-burdened health facilities. How MWHs are adapted during times of crisis may provide insights into what systems of care are more appropriate in meeting women's needs more broadly. Conclusion: The current global pandemic is an important time to reflect on whether MWHs are meeting the needs of a diverse range of women, in times of stability and during emergencies, and engage in genuine dialogue with women about the kinds of maternity care they want. We need to co-create those systems now so that they are more resilient during the inevitable crises we will face in the future.